The influence of normal fault geometry on igneous sill emplacement and morphology - Magee,C; Jackson,CAL; Schofield,N (Geology, 2013)
Magma flow within the subsurface is heavily influenced by the pre-existing structure of the upper crust. During continental rifting, normal faults modify the geometry of igneous networks by providing preferential pathways for the intrusion of magma. However, the mechanisms by which magma intrudes into fault planes is poorly understood. Here, we quantitatively document the relationship between fault architecture and intrusion distribution and geometry using 3D seismic reflection data from the Exmouth Sub-basin, offshore NW Australia. Inclined segments of saucer-shaped sills are observed to specifically intrude faults along positive fault-plane corrugations (i.e., convex-into-the-hangingwall). We suggest that stress field variations associated with the positive corrugations provide suitable conditions for fault reactivation as magma conduits. Pre-existing faults also modify sill geometries through the offset of stratigraphic horizons that may be preferentially intruded, potentially resulting in the formation of a new sill or the development of minor intrusive steps. This work emphasizes the importance of the pre-existing structural template in controlling the growth and final geometry of intrusive networks and, implicitly, the distribution of eruptive volcanic centers.